1994
DOI: 10.1177/036354659402200109
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Allograft Reconstruction in the Skeletally Immature Athlete

Abstract: The purpose of this study was to evaluate anterior cruciate ligament allograft reconstruction in skeletally immature athletes. Eight patients (mean age, 13 years, 6 months; range, 10 to 15 years) with radiographic documentation of open growth plates had anterior cruciate ligament repair and reconstruction with fascia lata or Achilles tendon allograft tissue. A 7-mm graft was centrally placed across the tibial physes and in an over-the-top position on the femur. All patients returned for followup a mean of 58 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
140
1
10

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(152 citation statements)
references
References 38 publications
1
140
1
10
Order By: Relevance
“…The graft is typically placed through a transphyseal tibial tunnel and then is fixed to the femur in an over-the-top position [46][47][48], or in epiphyseal tunnels [9,49].…”
Section: Partial Transphyseal Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The graft is typically placed through a transphyseal tibial tunnel and then is fixed to the femur in an over-the-top position [46][47][48], or in epiphyseal tunnels [9,49].…”
Section: Partial Transphyseal Techniquesmentioning
confidence: 99%
“…There was one leg length discrepancy due to accidental physeal stapling during graft fixation. Andrews et al [46] reported a series of 8 patients treated with transphyseal tibial tunnels and over-the-top femoral placement. They reported 6 excellent, 1 good and 1 fair result at an average of 58 months follow-up with no significant leg length discrepancies.…”
Section: Partial Transphyseal Techniquesmentioning
confidence: 99%
“…A análise da literatura em biomecânica a respeito dos substitutos citados permite notar que tem sido pouco estudado o perfil mecânico do tendão calcâneo, embora sua aplicação clinica venha sendo recomendada por diversos autores (1,5,12,17,18) .…”
Section: Introductionunclassified
“…If we focus our attention on adolescents with growth remaining (boys: 13-16 years; girls: 12-14 years), primary repair and extraarticular procedures are not recommended [10,11]. Intraarticular, however, extraphyseal techniques might be used in the treatment of ACL lesion in children and adolescents with wide-open physes and this seems to be a good option [16,17,19,26,29]. However, some investigators still report that the implant is not isometric [21] and anatomic [22], whereas others demonstrate a low rate of growth damage [19,20].…”
Section: Discussionmentioning
confidence: 99%